Improving Chocolate Quality and Safety Through Food Technology-Based Cocoa Processing Innovation - Yuhendra AP; Reza Kusuma Nurrohman; Mi’raj Fuadi; Satrijo Saloko; Rahmat Sabani; I Wayan Sweca Yasa; Joko Sumarsono; Setyaning Pawestri; Nur Afni; Qabul Dinanta Utama; Wiharyani Werdiningsih; Sukmawaty Sukmawaty; Guyup Mahardhian Dwi Putra; Diah Ajeng Setiawati; Surya Abdul Muttalib; Made Gendis Putri Pertiwi; Isnaini Puspitasari; Fakhrul Irfan Khalil; Fuad Sauqi Isnain; Endang Purnama Dewi; Elya Antariksana Bachmida; Wan Rosli Bin Wan Ishak; Haslina Ahmad (Universitas Mataram, 2026)
The increasing challenges faced by cocoa farmers in Kampung Cokelat Senare, particularly the decline in cocoa yields since 2020, have necessitated innovative interventions. This community service initiative focuses on improving cocoa processing techniques through food technology to enhance the quality and safety of locally produced chocolate. Expert involvement facilitates effective knowledge exchange essential for revitalizing the local cocoa industry. The primary objective of this initiative is to educate farmers on modern cocoa processing methods and food safety protocols to improve chocolate quality and promote sustainable production. The methodology includes structured workshops led by experts, including Prof. Wan Rosli Bin Wan Ishak, emphasizing optimized cocoa roasting techniques and hygienic processing practices. These activities are complemented by practical demonstrations and field visits to local cocoa processing facilities, enabling direct application of newly acquired knowledge. The initiative produced several notable outcomes. Farmers demonstrated improved understanding of cocoa roasting parameters, resulting in enhanced chocolate flavor profiles. In addition, improved safety measures during processing contributed to reduced aflatoxin contamination, addressing critical food safety concerns. The interactive workshop format increased participant engagement and encouraged adoption of modern techniques. Survey results indicated a positive change in farmers’ attitudes toward innovation and a commitment to applying these methods. Overall, this initiative has positioned the community toward more sustainable cocoa production, with expected improvements in product quality and economic resilience. The program highlights the importance of education, collaboration, and technology transfer in strengthening local cocoa-based industries.